Kewaspadaan petugas kesehatan terhadap lepra Analisis retrospektif pada penderita lepra DI RSUP DR. SARDJITO YOGYAKARTA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRAK The performance of health staff in early detection of leprosy plays an important role in the leprosy control programme. An indirect study of the awareness of health professionals was done through indepth interviews with all leprosy patient of the Dr. Sardjito Hospital duringJuly-December 1989 to find out whether they had reported at a clinic , at any time during the preceeding three years with suspected signs of leprosy, but without being diagnosed. . The result shows that leprosy was diagnosed after an average of 2 years of illness, and after an average of 4.5 visits to the health staff. Leprosy was misdiagnosed in 90% of the visits. Leprosy was detected by dermatologists in 87% of the patients, general practioners in 4%, other specialist in 4% and paramedical workers in 5%. The problem of low awareness toward leprosy is far from new and yet there is almost certainly no simple answer for this defect and is often neglected in the medical curriculum.